Multi-agent Orbit Design for Visual Perception Enhancement Purpose. (7th October 2014) - Nourzadeh, Hamidreza; McInroy, John
This paper develops a robust optimization-based method to design orbits on which the sensory perception of the desired physical quantities are maximized. It also demonstrates how to incorporate various constraints imposed by many spacecraft missions, such as collision avoidance, co-orbital configuration, altitude and frozen orbit constraints along with Sun-synchronous orbit constraints. The paper specifically investigates designing orbits for constrained visual sensor planning applications as its case study. For this purpose, the key elements to form an image in such vision systems are considered and effective factors are taken into account to define a metric for perception quality. The method employs a max-min model to ensure robustness against possible perturbations and model uncertainties. While fulfilling the mission requirements, the algorithm devises orbits on which a higher level collective observation quality for the desired sides of the targets is available. The simulation results confirm the effectiveness of the proposed method for several scenarios involving low and medium Earth orbits as well as a challenging space-based space surveillance program application.